2023
DOI: 10.3390/metabo13091023
|View full text |Cite
|
Sign up to set email alerts
|

Liver and Muscle Transcriptomes Differ in Mid-Lactation Cows Divergent in Feed Efficiency in the Presence or Absence of Supplemental Rumen-Protected Choline

Malia J. Caputo,
Wenli Li,
Sophia J. Kendall
et al.

Abstract: Improving dairy cow feed efficiency is critical to the sustainability and profitability of dairy production, yet the underlying mechanisms that contribute to individual cow variation in feed efficiency are not fully understood. The objectives of this study were to (1) identify genes and associated pathways that are altered in cows with high- or low-residual feed intake (RFI) using RNA sequencing, and (2) determine if rumen-protected choline supplementation during mid-lactation would influence performance or fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 101 publications
0
1
0
Order By: Relevance
“…When these cells encounter pathogens or microbial components like lipopolysaccharide, the upregulation of CD14 + cells can lead to enhanced phagocytosis, cytokine production, and activation of these myeloid cells as part of the innate immune response 19 . Even though all mid-lactating cows were healthy in this study, an increased expression of T cells, B cells, or monocytes suggest a state of activation and readiness for migration to infected tissues, which plays a crucial role in mounting effective immune responses against pathogens or antigens, and these findings are aligned to gene expression data of Caputo et al 15 . Studies conducted on low and high RFI pigs showed no discernible difference in immune response when exposed to a viral challenge 20 .…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…When these cells encounter pathogens or microbial components like lipopolysaccharide, the upregulation of CD14 + cells can lead to enhanced phagocytosis, cytokine production, and activation of these myeloid cells as part of the innate immune response 19 . Even though all mid-lactating cows were healthy in this study, an increased expression of T cells, B cells, or monocytes suggest a state of activation and readiness for migration to infected tissues, which plays a crucial role in mounting effective immune responses against pathogens or antigens, and these findings are aligned to gene expression data of Caputo et al 15 . Studies conducted on low and high RFI pigs showed no discernible difference in immune response when exposed to a viral challenge 20 .…”
Section: Discussionsupporting
confidence: 82%
“…In a previous study conducted in our laboratory, healthy mid-lactating cows were categorized based on RFI into HE (low RFI = − 1.73 kg/d) or LE (high RFI = + 1.72 kg/d), and RNA seq results indicated that the molecular control of gene expression in liver and muscle tissue were associated with immune function, and differed according to RFI ranking 15 . It was observed that several highly expressed genes involved in the activation of the innate and adaptive immune response were upregulated in HE cows ( LYZ , AOAH , CLEC7A , GIMAP8 , GIMAP6 , MARCO , and CD180 ) compared to LE cows 15 . In the present study, the increased expression of CD14 + cells were observed within CD11b + monocytes in HE cows compared to LE cows.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individual TMR ingredients were collected weekly and dried by forced air oven (Isotemp Oven, Fisher Scientific, Waltham, MA) at 55°C for 48 h (concentrates in triplicate, forages in quadruplicate), composited by week and analyzed by a commercial laboratory (Dairyland Labs, Inc., Arcadia, WI) as described previously ( 20 ). In brief, samples were analyzed for DM determined by National Forage Testing Association method 2.1.4, crude protein (method 990.03), neutral detergent fiber (method 2002.04), acid detergent fiber (method 973.18), lignin (method 973.18), ether extract (method 920.39), ash (method 942.05), water-soluble carbohydrates, and starch.…”
Section: Methodsmentioning
confidence: 99%